Pengaruh Praktik Pengalaman Lapangan Kependidikan dan Self-Efficacy Terhadap Kesiapan Menjadi Guru pada Mahasiswa Fakultas Tarbiyah Universitas Islam Zainul Hasan Genggong - Mariyatul Qibthiyah; Ainol, Ainol; Zaini, Bahruddin (Jurnal Kependidikan Islam, 2024)
The decision to enroll in a university is typically driven by the aspiration to become a well-prepared teacher. However, some potential educators may not feel entirely ready to embrace this profession. This study aims to assess how educational field experience influences individuals and explore the connection between self-confidence and teaching preparedness. Additionally, it seeks to examine how self-confidence and educational field experience together shape a person's readiness for a teaching career. The research adopts a quantitative approach, utilizing a method of sampling that includes all potential participants. Questionnaires were employed to gather data, the results of which were evaluated by use of a statistical method known as partial least squares structural equation modelling. The results of the research demonstrate a positive impact of both self-confidence and educational field experience on individuals' readiness and their desire to pursue teaching. In fact, the findings reveal that self-confidence and educational field experience significantly contribute to teacher readiness (0.581). Notably, this research offers a new viewpoint by emphasising the impact of self-confidence on one's preparedness to enter the teaching profession, as indicated by a weak F-Square test result of 0.053.